Business Management of Village-Owned Enterprises: A Case Study of a BUMDesa in Bali - Ida Ayu Nyoman Yuliastuti; I Gede Cahyadi Putra; I Dewa Made Arik Permana Putra (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
The purpose of this study is first to describe the management practices of Village-Owned Enterprises (BUMDesa) in running business units in the fields of agriculture and waste management through waste banks. Second, to identify the main challenges faced by BUMDesa in terms of institutions, business planning, accountability, and human resource management. Third, to formulate strategies to strengthen contextual and sustainable BUMDesa management, especially in the management of agricultural-based business units and waste processing businesses. The study was conducted at BUMDesa Asta Dharma, Sembung Gede Village. The research method is descriptive qualitative. The results of the study indicate that BUMDesa management has implemented good corporate governance, which applies the principles of transparency, accountability, efficiency, and participation. Transparency includes aspects of business activity planning, financial management, and performance reporting to the entire community. Accountability can be seen in financial accountability. Efficiency starts from the preparation of the work budget, implementation of activities, to the follow-up of the business process. Participation is carried out with the community as the subject, not the object involved in each business cycle. This encourages participation to become the main strategy in strengthening the resilience, inclusiveness, and desire of BUMDesa Asta Dharma